Effect of the sensitizer in polyvinylcarbazole (PVK) thermoelectret - DR. PANKAJ KUMAR MISHRA (International Journal of Pharma and Bio Sciences, 2017)
The major developments in polymer science during the past few decades have been enriching our knowledge about the relationship between the structure of polymers and their thermo-electrical properties. Pure and malachite green sensitized Polyvinylcarbazole (PVK) films have been prepared by solution caste technique. The absorption spectra, ultraviolet (UV) spectroscopy and energy dispersive x-rayEDX have been studied. At lower wavelengths i.e300 nm) absorption in pure PVK sample is found to be high and also confirm the decrement in visible range within the region. It also confirms that band gap of malachite green sensitized PVK decreases from 4.2 to 4.1 eV. The results of UV and EDX are obtained in pure and malachite green sensitized PVK samples. Understanding the changes in the morphology and the dynamic behavior of polymers and the resulting properties of the material is a prerequisite to any controlled processing and functioning, and for ensuring the long-term stability of these materials.